Temperature orchestrates phytoplankton community and environment in mountain stream for enhancing resource use efficiency - Ji, Li; Zhang, Huayong; Wang, Zhongyu; Tian, Yonglan; Tian, Wang; Liu, Zhao (Frontiers in Marine Science, 2025)
Warming is a key factor influencing the function of the structure and function of phytoplankton communities. However, the impacts of temperature on phytoplankton resource use efficiency (RUE) in mountain rivers remain poorly understood. Here, the spatiotemporal patterns of phytoplankton community structure (biomass, community composition, and diversity), function (RUE), and the main environmental factors in a high-latitude mountainous stream were investigated to assess how temperature affects the phytoplankton RUE. The results showed that phytoplankton species richness, biomass, and RUE all increased with rising temperature, with species richness significantly higher. There was a shift in the phytoplankton community from dominated by Cyanophyta at lower temperatures to dominated by Cryptophyta at higher temperatures. Phytoplankton RUE was significantly positively correlated to species richness, but no significant relationship was observed between RUE and Pielou’s evenness. Furthermore, redundancy analysis and Mantel tests revealed that water temperature, nutrient (TP, and NH4+-N) and physicochemical variable (flow velocity, and dissolved oxygen) explained 40.40% of the overall variation in phytoplankton RUE. Phytoplankton RUE exhibited stronger responses to environmental variables than phytoplankton biomass or diversity. The results highlighted that temperature directly affected phytoplankton community composition and enhanced RUE by altering environmental conditions and biodiversity. Temperature plays a crucial role in shaping the structure and function of phytoplankton communities in rivers. Our results contribute to the deep understanding of the mechanisms by which temperature influences RUE providing a basis for the sustainable management and conservation of aquatic ecosystems and watersheds.